A Clinical Decision Tree for Preserving versus Extracting a Compromised Tooth with Extensive Subgingival Caries or Crown Fractures - Moslemi, Neda; Farhadi, Elham; Farhadi, Mehdi (Regeneration, Reconstruction & Restoration (Triple R), 2024)
One of the most challenging issues in the field of dentistry is to decide whether to preserve or extract a compromised tooth with subgingival caries/crown fractures. Several patient-related factors (i.e. biological, behavioral, or financial factors), tooth-related factors (i.e. periodontal, endodontic, or restorative factors), and the role of the tooth in the overall treatment plan should be considered to make the most accurate decision. This article has focused on the decision-making process related to the management of compromised teeth with subgingival caries/crown fractures. Based on the current scientific evidence and clinical experience of the authors, an algorithm has been suggested to simplify this process of decision. In the first step, compromised teeth were classified as single-root or multi-root groups. “Crown-to-root ratio” (C/R ratio), and “apical extension of caries to the crestal bone” were considered the main clinical parameters in the decision-making process for single-root and multi-root teeth, respectively. We do not recommend restoring the compromised teeth if the C/R ratio is more than 1 (for single-root teeth) or if the extension of caries has reached the alveolar bone crest (for multi-root teeth). For maintainable single-root teeth, there are three treatment options to provide space for the re-establishment of supracrestal soft tissue attachment (previously named as biologic width) between the future restorative margin and underlying crestal bone. These approaches include: surgical crown lengthening (SCL), orthodontic forced eruption (OFE), and deep marginal elevation (DME). For multi-root teeth, SCL and DME are usually the procedures of choice. Multi-root teeth are not amenable to OFE due to the heavy orthodontic forces needed for extrusion. We also discussed the indications and limitations related to each treatment option. Further studies should be conducted to evaluate the external validity of this decision tree. Keywords: Decision trees; Decision making; Tooth fractures; Dental caries; Tooth extraction.